The Challenges of Conditional Cash Transfer (CCT) Program Implementation in the Philippines: The Case of Balindong, Lanao Del Sur - Ivy Sarah Mae Berowa-Arimao (International Journal of Advanced Science and Technology, 2020)
The paper has a descriptive research design and utilized a qualitative approach in studying the challenges in the implementation of Conditional Cash Transfer (CCT) or 4Ps in the Municipality of Balindong, Lanao Del Sur, Philippines. It used multi-stage sampling techniques and used only frequencies, percentages, and ranks in analyzing data obtained through a questionnaire supplemented by interviews with key informants. The findings reveal that there are gaps in the implementation of the program, about an inherent weakness in program design, with the implementation processes, with the program implementers such as the Municipal Links, others are due to the situation in the context of governance functions in the locality and the rest are due to the beneficiaries themselves. Some governance deficits have clear implications to local communities, andthe compliance of the beneficiaries with the conditionalities attached to the grant. However, despite challenges thus identified in this research endeavour, the program implementation in the Municipality of Balindong is generally considered to be very satisfactory. Keywords: Conditional Cash Transfer (CCT), conditionalities, program, implementation